Understanding the Role of Philosophy in Theology and Christian Religious Education - Yakup Hariyanto (International Journal of Christian Education and Philosophical Inquiry, 2025)
This study is motivated by the negative perception among some Christians who regard philosophy as a threat to faith and theology, even believing that it can undermine conviction and reduce the truth of Scripture. Using a qualitative research method based on a literature study that collects and analyzes various relevant sources, this research aims to re-examine the relationship between philosophy, theology, and Christian Religious Education, as well as to explore the constructive role of philosophy in enriching the understanding of faith. The findings reveal that philosophy functions as a preparation evangelica - a “rational foundation that prepares one to receive faith” - rather than as an antagonist. Furthermore, the study emphasizes that the integration of philosophy and theology produces a critical and reflective educational approach that deepens the knowledge of God and fosters a dynamic Christian Religious Education. Thus, this research offers a new perspective that reconciles philosophy and faith, and recommends ongoing dialogue between the two for the advancement of theology and Christian education.